Inert Liquid Encapsulation: A Novel Approach to Enhancing Lifetime, Thermal Stability, and Recyclability of Solar Cells - Jokikyyny, Tommi (My University, 2026)
The decreasing dependence on fossil fuels amplifies the significance of renewable energy sources. Photovoltaics play a crucial role in the field, and the efforts to improve them have largely focused on enhancing efficiency. Little attention has been given to one of the most important components of solar modules: encapsulation. Hence, the encapsulation of commercial solar modules has remained almost unchanged for decades, with the photovoltaic cell laminated into a crosslinked polymer material. This thesis presents a new way of encapsulating solar cells in inert materials that could significantly increase the lifetime of solar modules and facilitate easier recycling of the different components. This new encapsulation method paves the way for modular designs, with replaceable encapsulation materials and higher focus on the overall environmental impact of solar power. This thesis focuses on one main material while proposing other materials that pose wanted qualities. The material selected for the prototyping and experimental work was dimethylpolysiloxane. Multiple prototypes were created, and the plausibility of the designs was tested in real life conditions during the harshest weather in Finland as well as in controlled laboratory conditions. Notably, the performance of the prototype in outdoor weathering did not degrade during the testing period, despite temperature fluctuations from the warm summer sun to freezing temperatures, as well as copious amounts of snow resting on top of the prototype.

Uusiutuvien energianlähteiden tarve kasvaa fossiilisten polttoaineiden riippuvuuden vähentyessä. Aurinkoenergialla on merkittävä rooli alalla, mutta tutkimuksen kohteena on ollut lähinnä hyötysuhteen kasvattaminen. Aurinkopaneelien eliniän kannalta olennainen komponentti, enkapsulointi, on jäänyt vähemmälle huomiolle. Siten aurinkokennojen enkapsulointi on pysynyt samankaltaisena vuosikymmenet. Aurinkokenno laminoidaan ristisilloitetun polymeerin sisään. Tämä diplomityö esittelee uuden tavan enkapsuloida aurinkokennot inerttiin materiaaliin, joka voisi merkittävästi pidentää aurinkopaneelien elinikää samalla helpottaen niiden kierrätystä huomattavasti. Uusi enkapsulointitapa avaa tietä uusille modulaarisille kennoille, joissa enkapsulointimateriaali voidaan vaihtaa, keventäen kennojen negatiivisia ympäristövaikutuksia. Tässä työssä keskitytään yhteen potentiaaliseen materiaaliin, samalla ehdottaen muita korvaavia materiaaleja sopivilla ominaisuuksilla. Työhön valikoitunut materiaali on dimetyylipolysiloksaani. Useita prototyyppejä valmistettiin sekä kunkin kyvykkyys testattiin joko karuissa ulko-olosuhteissa tai laboratorio-olosuhteissa. Huomattavaa on, miten erityisesti ulkotestauksessa olleen prototyypin toiminta ei heikentynyt suurista lämpötilanvaihteluista huolimatta. Hetkittäin kenno oli suorassa auringonvalossa, ja muutaman viikon kuluttua 30 cm paksun lumikerroksen alla hyytävässä talvisäässä.
Keywords: Encapsulation; Solar energy; Solar cells; enkapsulointi; aurinkoenergia; aurinkopaneelit